Nilai-nilai Budaya Minangkabau dalam Novel Negeri 5 Menara Karya Ahmad Fuadi - Netri, Netri; Nurizzati, Nurizzati; Afnita, Afnita (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
This was a descriptive qualitative research which was aimed to describe the cultural values of Minangkabau in the Negeri 5 Menara novel by Ahmad Fuadi. The sources of data of this research were written data of Negeri 5 Menara novel itself. The findings of this research showed that there were 145 data of cultural values of Minangkabau in this novel which consist of 39 data related to the value of human relationship with the Creator, 41 data related to the value of human relationships with others, 28 data related to the value of fostering unity, and 30 data related to the value of consensus and agreement.